1993
DOI: 10.1177/00957984930194002
|View full text |Cite
|
Sign up to set email alerts
|

Culture and Social Outcomes among Inner-City African American Children: An Afrographic Exploration

Abstract: This study employs the Triple Quandaryframework as a paradigmfor describing the cultural orientations of 50 inner-city African American sixth graders. The implications of the relative endorsement of these orientations and some specific expressionsfor social outcomes of empathy, Machiavellianism, delinquency, and aggression were also examined. Three cultural orientations-Anglocultural, marginalized minority, and Afrocultural as well as the component Afrocultural expressions of spirituality, communalism, and aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
79
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 14 publications
10
79
0
Order By: Relevance
“…In addition, there has been a growing interest in the ways in which race-related and cultural factors might serve as protective and promotive influences in this population (Caldwell et al 2004;Jagers 1996;Jagers and Mock 1993;Jagers et al 2003;Ward 1995). However, we agree with Caldwell et al that there continues to be a need to systematically study these sociocultural influences as psychosocial or social contextual factors related to violent behavior.…”
Section: Protective Factors Against Violence Involvement: Toward a Cusupporting
confidence: 57%
See 1 more Smart Citation
“…In addition, there has been a growing interest in the ways in which race-related and cultural factors might serve as protective and promotive influences in this population (Caldwell et al 2004;Jagers 1996;Jagers and Mock 1993;Jagers et al 2003;Ward 1995). However, we agree with Caldwell et al that there continues to be a need to systematically study these sociocultural influences as psychosocial or social contextual factors related to violent behavior.…”
Section: Protective Factors Against Violence Involvement: Toward a Cusupporting
confidence: 57%
“…There is some evidence that a communal orientation is associated with positive outcomes among children and youth. For example, a communal orientation was found to be associated with cooperative academic attitudes, empathy (Humphries et al 2000;Jagers 1997;Jagers and Mock 1993), related characteristics like moral maturity (Humphries et al 2000) and pro-social interpersonal values such as helpfulness and forgiveness (Jagers and Mock 1995).…”
Section: Protective Factors Against Violence Involvement: Toward a Cumentioning
confidence: 99%
“…Communalism is inversely associated with violent behavior among African-American boys (Jagers et al, 2007) and with the use of externalizing coping strategies, which are thought to be driven by emotion or anger, among African-American adolescents (Scott, 2003). More generally, acceptance of Afrocentric values is related to lower levels of delinquency (Jagers & Mock, 1993). Given that communalism emphasizes connection to others as well as the needs of the group over individual needs, communalism may help to promote thriving.…”
Section: Communalismmentioning
confidence: 99%
“…Teaching the ways in which God plays a supportive role in adolescents' lives may also help to support the development of thriving among religiously involved African-American youth. The significant role of communalism in relation to thriving and faith supports the importance of creating a sense of interdependence and responsibility for friends and family (Jagers & Mock, 1993;Woods & Jagers, 2003) as well as conveying traditional African values (Banks, Hogue, Timberlake & Liddle, 1997). A note of caution: at least two studies have found an inverse relationship between religious involvement and GPA (grade point average) among urban youth (Pedersen et al, 2005;Schwarz, Cappella, & Seidman, 2015).…”
Section: Practicementioning
confidence: 99%
“…A few studies of race-differences in aggressive behavior provide limited evidence that African American youth, especially males, may differ from other groups of youth in aggressive responses to everyday social encounters (Yager & RotheramBorus, 2000). There is no evidence, however, that problem behavior among youth is related to simply being African American (Jagers, 1997;Jagers & Mock, 1993;Spencer & Depree, 1996). As the Surgeon General (USDHHS, 2001) asserts, risk markers such as race or ethnicity are frequently used as risk factors for violence, yet being African American has no causal relationship to violence.…”
mentioning
confidence: 99%